Applying methods of scientific inquiry into intelligence, security, and counterterrorism - Sari, Arif 1986 (Premier reference source, 2019)
"This book examines the foremost techniques of hidden link predictions in stochastic social networks. It deals, principally, with methods and approaches that involve similarity index techniques, matrix factorization, reinforcement models, graph representations and community detections"--